RECORDS ON CHILDHOOD: A VIEW FROM PRIMARY SCHOOL AND ITS ACTORS (TARAPACÁ, NORTE DE CHILE 1880 - 1922) - Silva, Benjamín (Revista de Historia Social y de las Mentalidades, 2025)
The main objective of this study is to develop the image of the childhood in the Tarapaca Province between 1880 and 1920. This is achived by the analysis of the teachers’ daily speech. The prim ary educational structure had the task of promoting the reason, inculcating the civilization symbols in an imaginary instruction system. Contradictions between the educational promise, channelled from the State and the authorities seated in Santiago, and t he fragile primary educational structure, are presented.
Keywords: Infancy; School Primary System; Teachers